Biomedical applications of wearable biosensors - Mais Haj Bakri; Ali Can Özarslan; Azime Erarslan; Yeliz Basaran Elalmis; Fatih Ciftci (Next Materials, 2024)
Over the last decade, both scientific and commercial communities have focused on developing wearable sensors for biomedical use. These sensors monitor vital signs in various individuals, including patients, athletes, infants, and the elderly. They contribute to mobile health technologies, offering real-time health recommendations and management. Wearable and implantable devices are reshaping healthcare, driven by sensor advancements. Biosensors, known for their simplicity and adaptability, hold significant potential. This review focuses on categorizing wearable biosensors, including classifying biological elements, nanomaterials, and transducers. It also examines the various types of wearable sensors, specialized sensor designs, applications in textile materials, wearable medical devices, and the advantages of biosensors in medicine. Comprehensive analysis of the various applications of wearable biotechnology while addressing the challenges and possible remedies associated with wearable technology were reviewed.